Effectiveness Of Environmental Law Enforcement Against Illegal Logging In Rokan Hulu Regency - Rabiuladawiyah Rabiuladawiyah; Budi Hartono; Fat Haryanto Lisda; Resti Hefriyenni (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
Illegal logging remains one of the major environmental challenges threatening forest sustainability in Indonesia, particularly in Rokan Hulu Regency, Riau Province. This study aims to examine the effectiveness of environmental law enforcement against illegal logging and to analyze whether its implementation is consistent with the principles of environmental legal protection, including the doctrine of ultimum remedium. This research employs a normative legal research approach using a statutory, conceptual, and doctrinal approach. The legal materials analyzed consist of primary legal materials, including Law No. 18 of 2013 concerning the Prevention and Eradication of Forest Destruction and Law No. 32 of 2009 concerning Environmental Protection and Management, supported by secondary legal materials comprising legal literature, scholarly journals, and official government documents. The collected legal materials were analyzed qualitatively through legal interpretation and descriptive-analytical methods. The findings indicate that environmental law enforcement against illegal logging in Rokan Hulu Regency is partially effective when assessed based on regulatory compliance, implementation of legal sanctions, and the achievement of environmental protection objectives. Although Indonesia has established a comprehensive legal framework for combating illegal logging, its implementation remains constrained by institutional capacity, inter-agency coordination, supporting facilities, and the continuing occurrence of environmental degradation. The study also concludes that the implementation of environmental law enforcement is generally consistent with the principles of environmental legal protection, including the doctrine of ultimum remedium. However, the application of ultimum remedium should be determined according to the statutory provisions governing each type of offence and should not be interpreted as requiring administrative sanctions before criminal prosecution in every illegal logging case.